Jump training in Rugby Union players: barbell or hexagonal bar? - Weakley, J. J.; Till, K.; Read, D. B.; Leduc, C.; Roe, G. A.; Phibbs, P. J.; Darrall-Jones, J.; Jones, B. (The Journal of Strength and Conditioning Research, 2021)
The countermovement jump (CMJ) is an exercise that can develop athletic performance. Using the conventional barbell (BAR) and hexagonal barbell (HEX) while jumping, the intensity can be increased. However, the bar that provides greater adaptations is unknown. Therefore, this study aimed to assess changes in loaded and unloaded CMJ with either a BAR or HEX across a 4-week mesocycle in rugby union players. Twenty-nine subjects were strength-matched and randomized into 2 groups. Subjects completed 3 sets of CMJ at 20% of 1 repetition maximum back squat, 3 times per week for 4 weeks, using either a BAR or HEX. Subjects completed an unloaded CMJ on a force plate before and after, whereas the highest peak concentric velocity during the jump squat was recorded in the first and last training sessions using a linear position transducer. Magnitude-based inferences assessed meaningful changes within- and between-groups. Possibly greater improvements in unloaded CMJ were found in the HEX group in jump height (effect size ± 90% confidence intervals: 0.27 ± 0.27), relative peak (0.21 ± 0.23), and mean power (0.32 ± 0.36). In addition, likely to very likely greater improvements were observed in the HEX group in peak velocity (0.33 ± 0.27), relative mean power (0.53 ± 0.30), mean force (0.47 ± 0.27), and 100-ms impulse (0.60 ± 0.48). Similar raw changes in jump squat peak velocity occurred (0.20-0.25 m/s), despite the likely greater ES occurring with the BAR (0.32 ± 0.26). These results indicate that training with the HEX leads to superior unloaded CMJ adaptations. In addition, practitioners should use either the HEX or BAR when aiming to enhance loaded jump ability.